PETA TEORITIK PENGKAJIAN TEATER: DARI TEORI STRUKTURALIS SAMPAI POSTRUKTURALIS - Novianto, Wahyu (Acintya, 2019)
AbstractThis article tries to map out the structuralist and poststructuralist theories as the basis of theater studies. So far, the studies of theater performed by theater academics have always been based on structuralist views; examining aspects of form, meaning, style and exclude the human aspects as forming agents of the structure. Structuralist view is antihumanist. It says that the sign has meaning when it is associated with other signs in a systematic unity of structure and not from its relation to the individu (artists). According to poststructuralist view, it is very possible to do a cultural study of theatrical text by looking at the interrelationship between one text and another outside, including social, cultural, literary, political, and other texts that are present randomly and overlapping (juxtaposition). Therefore, this theoretical mapping needs to be done in order to enrich the theater academics to conduct theater performances studies.Keywords: studies, theoretical map, structuralist, poststructuralist